Comparison of Clinical and Radiological Findings for Prediction of Scar Integrity in Women with Previous LSCS - Samina Qayyum, Saima Khan, Anila Mujdid Qureshi, Mehwish Mehmood, Mehwish Zafar, Ayesha Khalid, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: To compare the accuracy of clinical signs and radiological parameters in predicting scar integrity in women with a history of LSCS. Methods: This cross-sectional study was conducted at the Department of Gynaecology/ Obstetrics, Cantonment General Hospital, Rawalpindi from January 2022 to January 2023 and included 64 term pregnant women with prior cesarean delivery. Clinical features such as scar tenderness and onset of labor were recorded. Preoperative transabdominal ultrasound was used to measure lower uterine segment (LUS) and myometrial thickness and detect niche formation. Intraoperative findings at repeat cesarean delivery were used to determine scar integrity. Data were analyzed using SPSS version 26, with p-values <0.05 considered statistically significant. Results: Scar tenderness (p = 0.003) and induced or elective labor onset (p = 0.041) were significantly associated with dehiscent or thinned scars. On ultrasound, LUS thickness <2.5 mm and myometrial thickness <2 mm were strong predictors of scar defects, with sensitivities of 88.9% and 83.3%, respectively (both p < 0.001). Niche presence had the highest specificity (93.5%). Radiological markers outperformed clinical indicators in predictive accuracy. Conclusion: Ultrasound-based assessment, particularly measurement of LUS and myometrial thickness, provides a more reliable method for predicting scar integrity than clinical signs alone. Incorporating sonographic evaluation into pre-delivery planning can enhance maternal safety and guide the decision regarding mode of delivery. Keywords: LSCS scar integrity, lower uterine segment, ultrasound, scar dehiscence, clinical assessment, repeat cesarean, niche, uterine rupture prediction